Gualou Xiebai Banxia decoction ameliorates Poloxamer 407-induced hyperlipidemia. Issue 6 (25th June 2021) - Luo, Mingzhu; Fan, Rong; Wang, Xiaoming; Lu, Junyu; Li, Ping; Chu, Wenbin; Hu, Yonghe; Chen, Xuewei
Abstract: Ethnopharmacological relevance: Gualou Xiebai Banxia (GLXBBX) decoction is a well-known traditional Chinese herbal formula that was first discussed in the Synopsis of the Golden Chamber by Zhang Zhongjing in the Eastern Han Dynasty. In traditional Chinese medicine, GLXBBX is commonly prescribed to treat cardiovascular diseases, such as coronary heart disease and atherosclerosis. Objective: The present study aimed to examine GLXBBX's preventative capacity and elucidate the potential molecular mechanism of Poloxamer 407 (P407)-induced hyperlipidemia in rats. Materials and methods: Both the control and model groups received pure water, and the test group also received a GLXBBX decoction. For each administration, 3 ml of the solution was administered orally. To establish hyperlipidemia, a solution mixed with 0.25 g/kg P407 dissolved in 0.9% normal saline was injected slowly into the abdominal cavity. At the end of the study, the rats' plasma lipid levels were calculated using an automatic biochemical analyzer to evaluate the preventative capability of the GLXBBX decoction, and the serum and liver of the rats were collected. Results: The GLXBBX decoction significantly improved P407-induced hyperlipidemia, including increased plasma triglycerides (TGs), aspartate aminotransferase (AST) elevation, and lipid accumulation. Moreover, GLXBBX decoction treatment increased lipoprotein lipase (LPL) activity and mRNA expression of LPL. Furthermore, GLXBBX significantly suppressed the mRNA expression of stearoyl-CoA desaturase (SCD1). Conclusion: GLXBBX significantly improved P407-induced hyperlipidemia, which may have been related to enhanced LPL activity, increased LPL mRNA expression, and decreased mRNA expression of SCD1.